PENGARUH MODEL KOOPERATIF TIPE TALKING STICK BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V SDN 20 KALUMBUK - Fikli, Aprilia; Farhan Satria , Trinda; Marfilinda, Riri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low science learning outcomes of fifth-grade students of SDN 20 Kalumbuk. The purpose of this study was to determine the effect of the Talking Stick cooperative model assisted by Wordwall on the science learning outcomes of fifth-grade students of SDN 20 Kalumbuk. The study used a quantitative approach with a quasi-experimental type and a Posttest Only Control Group Design. The study population was all fifth-grade students of SDN 20 Kalumbuk. The results showed that the average learning outcomes of the experimental class were 83.70 while the control class was 76.92. The results of the hypothesis test showed that t count = 2.452 was greater than t table = 1.675 at a significance level of 0.05 so that H₀ was rejected and H₁ was accepted. This indicates that the Talking Stick cooperative model assisted by Wordwall had a significant effect on the science learning outcomes of fifth-grade students of SDN 20 Kalumbuk.